Measurement of prompt gamma production from neutron capture on manganese. (January 2023) - Czakoj, Tomáš; Košťál, Michal; Losa, Evžen; Novák, Evžen; Šimon, Jan; Schulc, Martin; Mravec, Filip; Cvachovec, František; Rataj, Jan; Matěj, Zdeněk
Abstract: Prompt gamma radiation is an important part of radiation fields with neutrons. Its good description is vital for precise predictions in void swelling issues because it is a contributor in gamma heating effect. The energy of prompt gamma rays is unique for each nuclide, thus can be used as its signature. Prompt gamma activation analysis is a technique using these gammas in nuclide identification. Despite the prompt gamma importance, current nuclear data libraries describe its origins very inaccurately. Measurement of gamma leakage spectrum of manganese bath with 252 Cf neutron source was performed using well-defined HPGe detector with high-density polyethylene shielding and stilbene scintillator. Stilbene measured gamma/neutron spectrum was separated by a Pulse Shape Discrimination method. MCNP6.2 simulation of the experiment was performed with ENDF/B-VIII.0 and JEFF-3.3 libraries for neutrons (and gamma production from neutron interactions) and MCPLIB04 library for photons. Analysis of results revealed that ENDF/B-VIII.0 and JEFF-3.3 description of prompt gamma radiation production is significantly discrepant. INDEN updated data for gamma production on 55 Mn was tested as well and show significant improvement compared to original ENDF/B-VIII.0 data. Nevertheless, significant discrepancies up to 50% were still observed. An alternative approach using prompt gamma production tables provided by IAEA was tested as well. Its results are basically in agreement with the calculation using INDEN updated 55 Mn data. Highlights: Prompt gamma leakage spectrum from manganese bath was measured by HPGe and stilbene. Simulation with present neutron data shows significantly discrepant gamma spectrum. INDEN updated data for gamma production on 55Mn shows significant improvement. Significant discrepancies up to 50% were still observed.